Influence of examiner's clinical experience on the reproducibility and accuracy of radiographic examination in detecting occlusal caries - Diniz, Michele Baffi [UNESP]; Rodrigues, Jonas Almeida; Neuhaus, Klaus W.; Cordeiro, Rita C. L. [UNESP]; Lussi, Adrian (Springer Heidelberg, 2010)
The aim of this in vitro study was to assess the influence of varying examiner's clinical experience on the reproducibility and accuracy of radiographic examination for occlusal caries detection. Standardized bitewing radiographs were obtained from 166 permanent molars. Radiographic examination was performed by final-year dental students from two universities (A, n=5; B, n=5) and by dentists with 5 to 7 years of experience who work in two different countries (C, n=5; D, n=5). All examinations were repeated after 1-week interval. The teeth were histologically prepared and assessed for caries extension. For intraexaminer reproducibility, the unweighted kappa values were: A (0.11-0.40), B (0.12-0.33), C (0.47-0.58), and D (0.42-0.71). Interexaminer reproducibility statistics were computed based on means +/- SD of unweighted kappa values: A (0.07 +/- 0.05), B (0.12 +/- 0.09), C (0.24 +/- 0.08), and D (0.33 +/- 0.10). Sensitivity, specificity, and accuracy were calculated at D(1) and D(3) thresholds and compared by performing McNemar test (p=0.05). D(1) sensitivity ranged between 0.29 and 0.75 and specificity between 0.24 and 0.85. D(3) specificity was moderate to high (between 0.62 and 0.95) for all groups, with statistically significant difference between the dentists groups (C and D). Sensitivity was low to moderate (between 0.21 and 0.57) with statistically significant difference for groups B and D. Accuracy was similar for all groups (0.55). Spearman's correlations were: A (0.12), B (0.24), C (0.30), and D (0.38). In conclusion, the reproducibility of radiographic examination was influenced by the examiner's clinical experience, training, and dental education as well as the accuracy in detecting occlusal caries.
Keywords: Dental caries; Occlusal caries detection; Radiographic caries diagnosis; Clinical experience; Bitewing radiographs